Study of J/psi production and cold nuclear matter effects in pPb collisions at √sNN=5 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Journal of high energy physics, 2014)
The production of J/ψ mesons with rapidity 1.5 < y < 4.0 or −5.0 < y < −2.5 and transverse momentum pT< 14 GeV/c is studied with the LHCb detector in proton-lead collisions at a nucleon-nucleon centre-of-mass energy $ \sqrt{{{s_{NN }}}} $= 5TeV. The J/ψ mesons are reconstructed using the dimuon decay mode. The analysis is based on a data sample corresponding to an integrated luminosity of about 1.6 nb−1. For the first time the nuclear modification factor and forward-backward production ratio are determined separately for prompt J/ψ mesons and J/ψ from b-hadron decays. Clear suppression of prompt J/ψ production with respect to proton-proton collisions at large rapidity is observed, while the production of J/ψ from b-hadron decays is less suppressed. These results show good agreement with available theoretical predictions. The measurement shows that cold nuclear matter effects are important for interpretations of the related quark-gluon plasma signatures in heavy-ion collisions.
Gesehen am 30.09.2020
Im Titel wird psi als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt